Raising our children to be resilient : a guide to helping children cope with trauma in today's world - Goldman, Linda, 1946- (Brunner-Routledge, 2005)
In this timely and much-needed book, Linda Goldman addresses the many frightening events that impact our children by providing the reader with a seamless mixture of theory and practice garnered from her extensive experience in the field. Raising Our Children to Be Resilient includes trauma resolution techniques and case studies, discussions of the respective roles played by parents, teachers and the larger community as well as additional resources for those in a position to help children who have been traumatized. The goal of Raising Our Children to Be Resilient is exactly wh.